Exhaled Breath Analysis in Tuberculosis Case Detection: The New Horizon - Pal, Ranabir; Dahal, S; Gurung, A (Nepal Journal of Epidemiology, 2013)
Sixty years ago, Nobel Prize winner Linus Pauling proposed the concept that human breath is a complex and dynamic gaseous mixture of more than 200 different endogenous volatile organic compounds (VOCs) that are continually being released in different quantities within the internal environment during health and disease. The researchers estimate that more than a thousand chemicals produced in different organ-systems as metabolic end products come out every minute through the respiratory tract. Volatile organic compounds and other products of oxidative stress are a big chunk among these exhaled breath elements. DOI: http://doi.dx.org/10.3126/nje.v3i2.8509